Sex-based considerations for implementation of ventricular assist device therapy - Jones-Ungerleider, K. Candis; Rose, Angela; Knott, Kevin; Comstock, Sarah; Haft, Jonathan W.; Pagani, Francis D.; Tang, Paul C. (Frontiers in Cardiovascular Medicine, 2022)
Women with advanced heart failure receive advanced surgical therapies such as durable left ventricular assist device (LVAD) implantation or heart transplantation at a rate much lower compared to males. Reasons for this discrepancy remain largely unknown. Much of what is understood reflects outcomes of those patients who ultimately receive device implant or heart transplantation. Females have been shown to have a higher mortality following LVAD implantation and experience higher rates of bleeding and clotting phenomena and right ventricular failure. Beyond outcomes, the literature is limited in the identification of pre-operative factors that drive lower than expected LVAD implant rates in this population. More focused research is needed to define the disparities in advance heart failure therapy delivery in women and other underserved populations.